The Performance of Employees of The Secretariat of The General and Public Relations Section In The Office of The Regional People's Representative Council (DPRD) Gorontalo City - Akhdan Ramadhan Badjeber; Ellys Rachman; Andi Yusuf Katili (Penerbit Jurnal Indonesia, 2024)
This study aims to determine the performance of employees of the secretariat of the general and public relations section at the Gorontalo City Regional People's Representative Council (DPRD) office. This type of research is descriptive research using a qualitative approach. Data collection techniques were conducted through interviews with a number of informants, observation and documentation. The research focus consists of discipline, ability and work environment The results showed that: 1) Employee discipline in the general and public relations section is not optimal because there are still some employees who are not disciplined about working time. due to lack of awareness of the responsibilities given even though each employee is bound by a Work Agreement (PK) which requires employees to be orderly in carrying out their duties to prepare secretarial administration and sterilize meeting or session rooms. 2) The ability of employees in the general and public relations sections is in accordance with their respective duties and functions but has not been maximized when carrying it out. Because there are still some employees who do not understand the tasks distributed, one of which is secretarial administration. 3) The work environment in the general and public relations section is not conducive because there is noise during working hours in the form of booming voices and music everywhere, making work disturbed.